Pengaruh Literasi Keuangan dan Impulsifitas terhadap Kinerja Keuangan Pribadi dengan Perilaku Keuangan sebagai Variabel Mediasi (Studi pada Mahasiswa Pengguna PayLater di Surabaya): Penelitian - Putri Risma; Raden Johnny Hadi Raharjo (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of financial literacy and impulsiveness on personal financial performance, with financial behavior acting as a mediating variable, among PayLater users in Surabaya. A quantitative approach was employed using a survey method involving 80 respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that financial literacy positively influences financial behavior, while impulsiveness has a significant negative effect. Financial behavior significantly mediates the relationship between impulsiveness and personal financial performance, but does not significantly mediate the relationship between financial literacy and personal financial performance. These results highlight the importance of controlling impulsive tendencies and fostering healthy financial behavior as a foundation for students' financial stability. The study suggests that financial education in universities should not only focus on conceptual understanding but also emphasize practical financial habits and self-regulation.